Characterizing the Credentialed Bachelor’s-Level Behavioral Health Support Workforce: A National Descriptive Study - Brianna M Lombardi; Lisa D Zerden; Maria Gaiser (Health Affairs Scholar, 2026)
Abstract Introduction Persistent shortages of the behavioral health workforce have prompted interest in expanding roles for bachelor’s-level behavioral health support workers as a strategy for increasing care. States vary in how they regulate this workforce. This study characterized how U.S. states define the bachelor’s-level behavioral health workforce through credentialing structures, educational requirements, and scope of practice. Methods Data were systematically abstracted from credentialing authorities, state administrative codes, state Medicaid programs, and government webpages using a standardized extraction guide. Results Twenty-nine states had at least one bachelor’s-level credential. A total of 50 credentials met inclusion criteria and were grouped into three categories: 20 licensed or certified credentials (9 states); 30 roles were defined solely in state administrative codes or other state guidance (22 states). Educational requirements differed across states, with most roles specifying degrees in human services or related fields and required practice hours ranging from zero to 10,000 hours of supervised experience. Nearly half of credentialed roles permitted multiple entry pathways, allowing work experience to substitute for formal education. Conclusion Findings reveal substantial variation in how states define and regulate this workforce, creating barriers to workforce planning, interstate mobility, and service delivery consistency.